Sustainability, supply chains, and defense - Powell-Turner, Julieanna; Murgatroyd, Clive (Palgrave Macmillan, 2021)
Integrating sustainability into the supply chain involves continual innovation and commitment from leaders and a realization that it is an indefinite process (Harrington, 2011). Defense supply chains are extensive and complex which require transparency, and long-term commitment rather than short termism that has dominated in the past! To facilitate this change, defense requires leaders to initiate change in the supply chain from a culture where the environment and societal issues have been given little consideration, to one where sustainability is considered throughout.
The Palgrave encyclopedia of interest groups, lobbying and public affairs
Keywords: Fourth Industrial Revolution; Rare earth elements (REE); Procurement; Defense; Recycling Resilience; Criticality; Circular economy; Sustainable supply chains